Implementación de una red piloto que muestre el funcionamiento y atributos que tiene el protocolo Overlay Transport Virtualization (OTV) sobre un ambiente virtualizado en GNS3 - Ramos Bastidas, Katherine Patricia (2016)
The following work is a technical report in which the processes for implementing a virtual environment of a corporate network in which the protocol Overlay Transport Virtualization (OTV) is used to integrate logically centers geographically distant data from a detailed efficiently and allows load balancing network in order to handle large volumes of data at low cost and in the shortest time possible. This document describes the most relevant information is to give a clear explanation of the protocol and its components such as the MAC, Mutihoming routing, virtual Interfaces with GRE tunnels, traffic labeled based on MPLS technology and its operation, to establish benefits of the protocol against the same type was created three topologies that allow highlight the attributes of OTV, in the first topology dynamic routing is used on links in order to establish the initial conditions of the network, in the second topology virtual interfaces VPN is used on links to take factors used to establish comparative tables against OTV, in the third topology finally the Overlay virtual network for links is implemented, once configured topologies passed the tests to collect data to establish technical results and draw conclusions.